2022
DOI: 10.3390/ijms23116267
|View full text |Cite
|
Sign up to set email alerts
|

Skin Minerals: Key Roles of Inorganic Elements in Skin Physiological Functions

Abstract: As odd as it may seem at first glance, minerals, it is what we are all about…or nearly. Although life on Earth is carbon-based, several other elements present in the planet’s crust are involved in and often indispensable for functioning of living organisms. Many ions are essential, and others show supportive and accessory qualities. They are operative in the skin, supporting specific processes related to the particular situation of this organ at the interface with the environment. Skin bioenergetics, redox bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 178 publications
0
7
0
2
Order By: Relevance
“…Mineral elements, when present in living tissues, are predominantly in an ionized state, dissolved within bodily fluids, as opposed to a dry mineral composition (Haftek et al 2022 ). Keratinocytes and fibroplasts are structures responsible for up to 80% of ionic transport through viable skin (Denda et al 2003 ; Paweloszek et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mineral elements, when present in living tissues, are predominantly in an ionized state, dissolved within bodily fluids, as opposed to a dry mineral composition (Haftek et al 2022 ). Keratinocytes and fibroplasts are structures responsible for up to 80% of ionic transport through viable skin (Denda et al 2003 ; Paweloszek et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…These include elements such as arsenic (As), boron (B), chromium (Cr), nickel (Ni), strontium (St), vanadium (V), as well as aluminum (Al), zirconium (Zr), silver (Ag), gold (Au), mercury (Hg), and silicon (Si). Haftek et al ( 2022 ) illustrated the distribution of predominant minerals within the human epidermis through a schematic drawing, based on literature data. Sodium (Na), S, K, P, Ca, Zn, and iron (Fe) were reported in relative concentrations (mg/g).…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Previous studies have shown that the epidermal iron content is highest in the basal layer, which is the site of proliferation of keratinocytes. 5 Iron metabolism in the skin is very finely tuned and numerous proteins involved in this process have been identified. 6 Recently, Asano et al demonstrated the iron recovery system in the human epidermis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we investigated the mechanism of epidermal thickening and pigmentation by examining the abnormal turnover caused by dysregulation of iron metabolism. Iron is required for adenosine triphosphate generation in the mitochondria for cell proliferation and has been shown to be involved in the process of keratinocyte proliferation and differentiation in the epidermis 4,5 . Previous studies have shown that the epidermal iron content is highest in the basal layer, which is the site of proliferation of keratinocytes 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation